Cereal Systems Initiative for South Asia (CSISA) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
CSISA provides an overall strategy and a new umbrella for contributing new science and technologies to accelerating short- and long-term cereal production growth in South Asia’s most important grain baskets. Through creating and facilitating innovative public-private sector partnerships in key 'hubs', (i.e. a geographic location that serves as a focal point for innovation in a target region) the project boosts the deployment of existing varieties, hybrids, crop management technologies, and market information. Each hub has a centralized location that serves as the point for research, innovation, extension, and participatory technology adaptation in the target region.